Continuous 24-hour intravenous infusion of recombinant human growth hormone (GH)-releasing hormone-(1-44)-amide augments pulsatile, entropic, and daily rhythmic GH secretion in postmenopausal women equally in the estrogen-withdrawn and estrogen-supplemented states - Evans, W S; Anderson, S M; Hull, L T; Azimi, P P; Bowers, C Y; Veldhuis, J D (The journal of clinical endocrinology and metabolism, 2001)
How estrogen amplifies GH secretion in the human is not known. The present study tests the clinical hypothesis that estradiol modulates the stimulatory actions of a primary GH feedforward signal, GHRH. To this end, we investigated the ability of short-term (7- to 12-day) supplementation with oral estradiol vs. placebo to modulate basal, pulsatile, entropic, and 24-h rhythmic GH secretion driven by a continuous iv infusion of recombinant human GHRH-(1--44)-amide vs. saline in nine healthy postmenopausal women. Volunteers underwent concurrent blood sampling every 10 min for 24 h on four occasions in a prospectively randomized, single blind, within-subject cross-over design (placebo/saline, placebo/GHRH, estradiol/saline, estradiol/GHRH). Intensively sampled serum GH concentrations were quantitated by ultrasensitive chemiluminescence assay. Basal, pulsatile, entropic (feedback-sensitive), and 24-h rhythmic modes of GH secretion were appraised by deconvolution analysis, the approximate entropy (ApEn) statistic, and cosine regression, respectively. ANOVA revealed that continuous iv infusion of GHRH in the estrogen-withdrawn (control) milieu 1) amplified individual basal (P = 0.00011) and pulsatile (P < 10(-13)) GH secretion rates by 12- and 11-fold, respectively; 2) augmented GH secretory burst mass and amplitude each by 10-fold (P < 10(-11)), without altering GH secretory burst frequency, duration, or half-life; 3) increased the disorderliness (ApEn) of GH release patterns (P = 0.0000002); 4) elevated the mesor (cosine mean) and amplitude of the 24-h rhythm in serum GH concentrations by nearly 30-fold (both P < 10(-12)); 5) induced a phase advance in the clocktime of the GH zenith (P = 0.021); and 6) evoked a new 24-h rhythm in GH secretory burst mass with a maximum at 0018 h GH (P < 10(-3)), while damping the mesor of the 24-h rhythm in GH interpulse intervals (P < 0.025). Estradiol supplementation alone 1) increased the 24-h mean and integrated serum GH concentration (P = 0.047); 2) augmented GH secretory burst mass (P: = 0.025) without influencing pulse frequency, duration, half-life, or basal secretion; 2) stimulated more irregular patterns of GH release (higher ApEn; P = 0.012); and 3) elevated the 24-h rhythmic GH mesor (P = 0.0005), but not amplitude. Notably, combined stimulation of the GH axis with GHRH-(1--44)-amide and estradiol exerted no further effect beyond that evoked by GHRH alone, except for normalizing the acrophase of 24-h GH rhythmic release and elevating the postinfusion plasma insulin-like growth factor I concentration (P = 0.016). Unexpectedly, the two GHRH-infused serum GH concentration profiles monitored after placebo and estradiol pretreatment showed strongly nonrandom synchrony with a 20- to 30-min lag (P < 0.001). In summary, the present clinical investigations unmask a 3-fold (pulsatile, entropic, and daily rhythmic) similitude between the neuroregulatory actions of estradiol and GHRH in healthy postmenopausal women. However, GHRH infusion was multifold more effectual than estradiol, and only GHRH elevated nonpulsatile (basal) GH secretion, shifted the GH acrophase, and synchronized GH profiles. Given the nonadditive nature of the joint effects of estradiol and GHRH on pulsatile and entropic GH release, we hypothesize that estrogen amplifies GH secretion in part by enhancing endogenous GHRH release or actions. In addition, the distinctive ability of GHRH (but not estradiol) to increase basal (nonpulsatile) GH secretion, shift the GH acrophase and synchronize GH output patterns identifies certain divergent hypothalamo-pituitary actions of these two major GH secretagogues.